2000
DOI: 10.1161/01.str.31.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypervolemic Therapy on Cerebral Blood Flow After Subarachnoid Hemorrhage

Abstract: Background and Purpose-Cerebral blood flow (CBF) is reduced after subarachnoid hemorrhage (SAH), and symptomatic vasospasm is a major cause of morbidity and mortality. Volume expansion has been reported to increase CBF after SAH, but CBF values in hypervolemic (HV) and normovolemic (NV) subjects have never been directly compared. Methods-On the day after aneurysm clipping, we randomly assigned 82 patients to receive HV or NV fluid management until SAH day 14. In addition to 80 mL/h of isotonic crystalloid, 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
222
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(228 citation statements)
references
References 68 publications
2
222
0
4
Order By: Relevance
“…5,15) Vasospasm is known to occur more often and with greater severity if the initial grade of injury is high. SAH invariably induces cerebral vasospasm within 3 weeks of the initial ictus.…”
Section: Introductionmentioning
confidence: 99%
“…5,15) Vasospasm is known to occur more often and with greater severity if the initial grade of injury is high. SAH invariably induces cerebral vasospasm within 3 weeks of the initial ictus.…”
Section: Introductionmentioning
confidence: 99%
“…2,17 In contrast, triple-H therapy has been shown to not be superior to normovolemic fluid therapy in the prevention of DCI. 5 Moreover, Lennihan et al 19 have reported that triple-H therapy does not increase cerebral blood flow. Therefore, it is necessary to validate the benefits of triple-H therapy and clarify the characteristics of systemic circulation after SAH.…”
mentioning
confidence: 99%
“…Some studies have suggested that triple-H therapy increases the incidence of heart failure and pulmonary edema in patients with SAH. 5,19,38 Pulmonary edema is common after SAH; neurogenic pulmonary edema may occur in the acute phase of SAH. Moreover, pulmonary edema associated with SAH has a variety of causes.…”
mentioning
confidence: 99%
“…Induced hypervolemia has been investigated in two prospective randomized trials -no benefit was found in vasospasm or clinical outcome [33,34]. Therefore, our clinical practice is to target euvolemia.…”
Section: Volume Statusmentioning
confidence: 99%